Associations between prefrontal γ-aminobutyric acid concentration and the tryptophan hydroxylase isoform 2 gene, a panic disorder risk allele in women - Preuss, Nora; Salehi, Basira; van der Veen, Jan Willem; Shen, Jun; Drevets, Wayne C.; Hodgkinson, Colin; Goldman, David; Hasler, Gregor (The international journal of neuropsychopharmacology, 2013)
Associations between the central serotonergic and γ-aminobutyric acid (GABA) systems play key roles in the prefrontal cortical regulation of emotion and cognition and in the pathophysiology and pharmacotherapy of highly prevalent psychiatric disorders. The goal of this study was to test the effects of common variants of the tryptophan hydroxylase isoform 2 (TPH2) gene on GABA concentration in the prefrontal cortex (PFC) using magnetic resonance spectroscopy. In this study involving 64 individuals, we examined the associations between prefrontal cortical GABA concentration and 12 single nucleotide polymorphisms (SNPs) spanning the TPH2 gene, including rs4570625 (−703 G/T SNP), a potentially functional TPH2 polymorphism that has been associated with decreased TPH2 mRNA expression and panic disorder. Our results revealed a significant association between increased GABA concentration in the PFC and the T-allele frequencies of two TPH2 SNPs, namely rs4570625 (−703 G/T) and rs2129575 (p⩽0.0004) and the C-allele frequency of one TPH2 SNP, namely rs1386491 (p = 0.0003) in female subjects. We concluded that rs4570625 (−703 G/T), rs2129575 and rs1386491 play a significant role in GABAergic neurotransmission and may contribute to the sex-specific dysfunction of the GABAergic system in the PFC.